The role of visual cues in eWOM on consumers’ behavioral intention and decisions - Filieri, Raffaele; Lin, Zhibin; Pino, Giovanni; Alguezaui, Salma; Inversini, Alessandro (Journal of business research, 2021)
•This study focuses on visual and verbal cues in eWOM.•We study the effect of visual and verbal cues on consumer intention and behavior.•We draw upon Dual Coding Theory and use a mixed-method approach.•Popularity and performance visual heuristics affect intentions and decision.•User-generated pictures also affect consumers’ intentions and decision. Consumers increasingly use eWOM to make decisions about various products and services. However, few studies have investigated how different visual and verbal eWOM cues affect the intention and decision to visit tourist destinations and their attractions. The current study fills this gap by drawing on Dual Coding Theory and investigating the influence of verbal and visual eWOM cues on consumers’ intention and behavior. The findings of a field study and an experimental study revealed that eWOM mainly affects tourists’ intentions and decisions through visual cues. Specifically, popularity heuristics, performance visual heuristics, and user-generated pictures affect tourists’ intention and decision to visit a destination and its attractions. Interestingly, information quality did not affect tourists’ decisions. The study offers important theoretical and managerial implications.